Adobe Flash Application To Improve Learning Outcomes Of Handball Courses For Students Of Physical Education Study Program FKIP UNIB - Yarmani, Yarmani; Syafrial, Syafrial; Ilahi, Bogy Restu; Defliyanto, Defliyanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
Research on Adobe Flash Applications To Improve Learning Outcomes of Handball Courses for Students of Physical Education Study Program FKIP UNIB aims to improve learning outcomes in handball courses as well as to determine the effectiveness of Adobe applications in learning handball. The method used in this study is (Classroom Action Research), the results of this study are descriptive because in this study a description will be produced about the extent to which handball learning has been improved by using Adobe Flash in physical education students of FKIP UNIB. The sample of this research is the third semester students of Physical Education Study Program, totaling 24 people. The data analysis technique used in this study is descriptive statistics in the form of percentages presented in tables or graphs. The results of this study are students can improve learning outcomes in handball courses. This can be seen from the percentage results which show that at the time of the pre-cycle an average score of 62.50 was obtained, with 7 students getting a complete score of 29%. In the first cycle, the average score was 67.10 with 12 people completing the 50% percentage. And in the second cycle showed significant results with completeness reaching 21 students out of 24 students getting a percentage of 87.5%. From these results it shows that student learning outcomes increase after learning using Adobe Flash is applied..